Research on the development path of China's digital trade under the background of the digital economy. Issue 1 (8th February 2022) - Li, Boning; Zhang, Su
Abstract : Purpose: The purpose of this study is to explore how the development of digital trade can provide new development prospects to China's foreign trade under the background of the gradual expansion of China's digital economy and the further release of policy dividends. Design/methodology/approach: Using the methods of literature collection and induction, combined with traditional trade theory, this paper analyzes the characteristics and challenges of digital trade under the background of the digital economy. Findings: The findings reveal that China's digital trade development still faces some risks, such as the containment of China's core technology, digital security and unbalanced development among regions. Considering these risks, China should break through core technical problem, participate in the formulation of international rules to ensure data security, give priority to the development of service trade and improve the unbalanced development of digital trade. Social implications: By analyzing the development status and characteristics of the digital economy and digital trade, this paper summarizes the challenges and comparative advantages faced by China's digital trade, and puts forward corresponding suggestions. These suggestions will allow China to take advantage of its rapid digital economy development and occupy a leading position in global digital trade. Originality/value: This paper creatively expounds on the new development direction of digital trade from the perspective of comparative advantage and risks, and provides some suggestions to expedite China's digital trade development.